(untitled) (Annals of Medical Research, 2021)
Aim: In our study, it was aimed to determine the usability of the inexpensive, fast and easily accessible platelet index, NLR (Neutrophil to Lymphocyte ratio) and PLR (Platelet to Lymphocyte ratio) as predictive values in patients with differentiated thyroid cancer and nodular hyperplasia. Materials and Methods: The data of 454 patients operated due to differentiated thyroid cancers and nodular hyperplasia at our clinic between 2010 and 2020 and a control group consisting of 120 healthy individuals were retrospectively examined. The data of the patients and the control group were statistically analyzed. Results: The study included a total of 574 participants including 314 patients who received differentiated thyroid cancer surgery, 140 patients who received surgery due to thyroid nodular hyperplasia and a control group consisting of 120 healthy individuals. There was no significant difference among the groups in terms of age. There was a dominance of the female sex among the groups, but the difference was insignificant. There was no significant difference among the groups in terms of their MPV, PLR or NLR values. However, the PDW (Platelet Distribution Width) values were significantly higher among the differentiated thyroid cancer patients. Conclusion: In our study, we observed that the MPV, PLR and NLR values varied, but the differences were not statistically significant. The PDW values were significantly high. Considering the current literature, we concluded that, among the existing parameters, NLR is a more reliable constant value at the stage of diagnosis.